HOTEL GREEN SPACES AS A NATURE-BASED SOLUTION INFLUENCE TO GUEST MENTAL HEALTH, WELLBEING AND SATISFACTION (Proceedings of International Educators Conference, 2023)
Since plenty of tourists prefer to stay at environmentally friendly hotels is growing rapidly, green spaces in hotels are becoming increasingly important. The present research is designed in order to learn the influence of green spaces on the visitors’ mental health, wellbeing and satisfaction in the hotel industry. An academic literature search was conducted for studies and review of the effects of green spaces.